Gamma-Irradiated Fowl Cholera Mucosal Vaccine: Potential Vaccine Candidate for Safe and Effective Immunization of Chicken Against Fowl Cholera - Dessalegn, Bereket; Bitew, Molalegne; Asfaw, Destaw; Khojaly, Esraa; Ibrahim, Saddam Mohammed; Abayneh, Takele; Gelaye, Esayas; Unger, Hermann; Wijewardana, Viskam (Frontiers in Immunology, 2021)
Fowl cholera (FC) caused by Pasteurella multocida is among serious infectious diseases of poultry. Currently, formalin inactivated FC (FI-FC) vaccine is widely used in Ethiopia. However, reports of the disease complaint remain higher despite the use of the vaccine. The aim of this study was to develop and evaluate gamma-irradiated mucosal FC vaccines that can be used nationally. In a vaccination-challenge experiment, the performance of gamma irradiated P. multocida (at 1kGy) formulated with Montanide gel/01 PR adjuvant was evaluated at different dose rates; 0.5 ml and 0.3ml, and routes; intranasal, intraocular and oral, in comparison with FI-FC vaccine in chicken. Chickens received three doses of the candidate vaccine at three-week intervals. Sera, and trachea and crop lavage were collected to assess the antibody levels using indirect and sandwich ELISAs, respectively. Challenge exposure was conducted by inoculation at 3.5×109 CFU/ml of P. multocida biotype A intranasally two weeks after the last immunization. Repeated measures ANOVA test and Kaplan Meier curve analysis were used to examine for statistical significance of antibody titers and survival analysis respectively. Sera IgG and secretory IgA titers were significantly raised after second immunization (p=0.0001). Chicken survival analysis showed that intranasal and intraocular administration of the candidate vaccine at the dose of 0.3 ml resulted in 100% protection as compared to intramuscular injection of FI-FC vaccine which conferred 85% protection (p=0.002). In conclusion, the results of this study showed that gamma-irradiated FC mucosal vaccine is safe and protective indicating its potential use for immunization of chicken against FC.